Desain Produk, Citra Merek, Promosi Dan Kualitas Produk Terhadap Loyalitas Pelanggan Amdk Merek Sanford - Fitriana, Rahmah; Iranita, Iranita; Jalal, Abdul (Bahtera Inovasi, 2023)
This study aims to explain Product Design, Brand Image, Promotion and Product Quality on Customer Loyalty of Sanford brand bottled water. The population in this study were 227,663 people in Tanjungpinang City. Sampling using techniques based on chance (incedental sampling). The sample in this study were people who happened to use Sanford brand bottled drinking water (AMDK) products, so that a research sample of 100 people was obtained. This type of research is quantitative research. Primary research data comes from questionnaires. The data collected and tested using Smart PLS 3.0 software. The results of the study found that product design has no effect on customer loyalty, brand image has no effect on customer loyalty, promotion has an effect and is significant on customer loyalty, product quality has an effect on customer loyalty. Based on the results of hypothesis testing, the influential and significant value is found in the promotion variable (X3) on customer loyalty (Y), obtained a t-statistic value of 8.108> t-table 1.66 and a p-value of 0.000 < a significance value of 0.05. Based on the results of the coefficient determination or goodness of fit (R2) test, a value of 0.688 (68.8%) is obtained. Indicates that this research model is strong because it is able to explain 68.8% of the overall research. While the remaining 31.2% is explained by other variables not examined in this study.